2020
DOI: 10.1007/978-3-030-45724-2_14
|View full text |Cite
|
Sign up to set email alerts
|

OptORAMa: Optimal Oblivious RAM

Abstract: Oblivious RAM (ORAM), first introduced in the ground-breaking work of Goldreich and Ostrovsky (STOC ’87 and J. ACM ’96) is a technique for provably obfuscating programs’ access patterns, such that the access patterns leak no information about the programs’ secret inputs. To compile a general program to an oblivious counterpart, it is well-known that amortized blowup is necessary, where N is the size of the logical memory. This was shown in Goldreich and Ostrovksy’s original O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…Recent advances in ORAM. Recently, [47], [6] proposed novel ORAM constructions, with improved efficiency matching the theoretical optimal overhead of O(log N ). It is possible to modify these to yield oblivious maps, thus asymptotically improving our schemes SD d and QOS as well as [27], [10], [29].…”
Section: B Related Workmentioning
confidence: 99%
“…Recent advances in ORAM. Recently, [47], [6] proposed novel ORAM constructions, with improved efficiency matching the theoretical optimal overhead of O(log N ). It is possible to modify these to yield oblivious maps, thus asymptotically improving our schemes SD d and QOS as well as [27], [10], [29].…”
Section: B Related Workmentioning
confidence: 99%
“…ORAMs are a powerful primitive that enable access to storage hosted by a potentially untrusted server such as a cloud storage provider without leaking any information beyond the number of accesses. As a result, there has been a lot of work in ORAM [3,24,39,46,53] leading to logarithmic overhead constructions. Furthermore, ORAM lower bounds [41,48] have shown that these are the best possible constructions.…”
Section: Comparison To Previous Workmentioning
confidence: 99%
“…In 1987, Goldreich proposed a seminal concept called ORAM, or Oblivious RAM (Random Access Memory), which can theoretically hide the content of data and their access patterns [28,29]. Many variations of ORAMs have been proposed since then [2,15,20,38,57,58,70,71,74].…”
Section: Succinct Oblivious Rammentioning
confidence: 99%
“…Hash-based ORAMs utilize hierarchical hash techniques based on one-way functions. They include the original Goldreich's Square-Root ORAM (SR-ORAM) [28,29] and many succeeding ORAMs [2,38,58]. In contrast, treebased ORAMs maintain data in tree data structures [57,71,74].…”
Section: Succinct Oblivious Rammentioning
confidence: 99%
See 1 more Smart Citation